Becoming Her Man: Transcoding in Medieval Marian Literature. - Koppelman, Kate (Exemplaria)
This essay argues that the Middle English miracles and lyrics of the Virgin Mary borrow the language of chivalry and courtly love in their depiction of the intercessory powers of the Mother of God. Because both chivalry and courtly love bear evidence of signifying contestation during the late Middle Ages, Marian texts that use the language of both or either can themselves be seen as complex and potentially anxiogenic. Understood through the theories of Gilles Deleuze and Felix Guattari, the miracles themselves can be defined as documents of signifying alliance or as evidence of what Deleuze and Guattari call “becoming.” Thus, the miracles and lyrics of the Virgin that use such fraught codes present us with an image of Mary that is unstable. An examination of such signifying alliances helps us better understand both the signifying networks at play in the later Middle Ages and the language work produced by them.